FAKTOR–FAKTOR YANG MEMPENGARUHI KESEDIAAN BERBELANJA SECARA ONLINE PADA GURU SEKOLAH DASAR (SD) KABUPATEN BANTUL - Cahyaningrum, Bambang Nur; Wijayanti, Ariyani Wahyu (Universitas Muhammadiyah Yogyakarta, 2017)
The Internet is an electronic means, which can be used for various activities, such as: communication, research, or other business transactions. Internet technology connects thousands of individual computer networks and organizations, worldwide. There are at least six reasons why internet technology is so popular. The six reasons are: the internet has wide connectivity and range, can reduce communication costs, lower transaction costs, can reduce agency costs, interactive, flexible, easy, and have the ability to distribute knowledge more quickly. Online shopping is more interesting with the ever-expanding Internet deployment, at this time. The study looked at whether: risk factors, benefit perceptions, perceptions of ease of use, and reputation perceptions affect consumer confidence in online shopping, as well as to know whether trust affects the willingness to shop online. Population and sample research, is elementary school teacher (SD) in Bantul regency. Data analysis in this research is done by SEM (Structural Equation Model). Respondents were 150 respondents. Perceptions of social trust, perception of benefits, perceptions of ease of use have a positive effect on trust. Risk perception has a negative relationship to trust. Perception of reputation has no positive effect on trust. Trust positively affects the willingness to buy online.